2013
DOI: 10.5194/hess-17-5013-2013
|View full text |Cite
|
Sign up to set email alerts
|

Developing predictive insight into changing water systems: use-inspired hydrologic science for the Anthropocene

Abstract: Abstract.Globally, many different kinds of water resources management issues call for policy-and infrastructure-based responses. Yet responsible decision-making about water resources management raises a fundamental challenge for hydrologists: making predictions about water resources on decadal-to century-long timescales. Obtaining insight into hydrologic futures over 100 yr timescales forces researchers to address internal and exogenous changes in the properties of hydrologic systems. To do this, new hydrologi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
87
0
2

Year Published

2014
2014
2015
2015

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 129 publications
(90 citation statements)
references
References 238 publications
1
87
0
2
Order By: Relevance
“…The needs to predict and to understand watershed behavior in areas without long gauging records (Sivapalan, 2003) and under changing conditions (Sivapalan, 2012) requires new theories that go beyond the mechanics of runoff generation and focus on understanding the underlying climatic and landscape properties that control those mechanics (Sivapalan, 2005;McDonnell et al, 2007;Wagener et al, 2013;Thompson et al, 2013). Wagener et al (2013) argued for the need for a "Darwinian" approach to prediction in ungauged basins, and discuss many of the concepts and approaches that have been given the term "Darwinian".…”
Section: Harman and P A Troch: What Makes Darwinian Hydrology "Dmentioning
confidence: 99%
See 1 more Smart Citation
“…The needs to predict and to understand watershed behavior in areas without long gauging records (Sivapalan, 2003) and under changing conditions (Sivapalan, 2012) requires new theories that go beyond the mechanics of runoff generation and focus on understanding the underlying climatic and landscape properties that control those mechanics (Sivapalan, 2005;McDonnell et al, 2007;Wagener et al, 2013;Thompson et al, 2013). Wagener et al (2013) argued for the need for a "Darwinian" approach to prediction in ungauged basins, and discuss many of the concepts and approaches that have been given the term "Darwinian".…”
Section: Harman and P A Troch: What Makes Darwinian Hydrology "Dmentioning
confidence: 99%
“…Rather than being used to predict the future evolution of landscapes or reproduce the precise form of a particular landscape, these models allow for testing of hypotheses to do with the relationship between the cumulative effects of processes interacting over time and in space. As Thompson et al (2013) suggest, this co-evolution modeling is not limited to landform and soil evolution over geologic timescales but can also include the development of ecological and human coupled systems, if the appropriate parameterizations can be developed and properly tested. Such models could help evaluate the "reachability" requirement of the Darwinian hypothesis and quantify the relative duration of different configurations of landscapes.…”
Section: Extrapolating Mechanisms: Co-evolution Modelingmentioning
confidence: 99%
“…Likewise, humanistic approaches to the study of water-law, philosophy, history, and ethics-can be further integrated with scientific knowledge [Wescoat, 2013]. The most effective way to create such a new discipline is to frame it as use-inspired science [Stokes, 1997;Clark and Dickson, 2003;Thompson et al, 2013], focused on addressing urgent water…”
Section: Need For a Water Focus On Sustainability Sciencementioning
confidence: 99%
“…They found that people in less developed sites had small-scale, decentralized, community-based water management solutions, while people in more developed sites favored large-scale, centralized, infrastructure and regulatory solutions. A conceptual framework for undertaking such comparative studies was presented in Thompson et al (2013), although the challenges inherent in this approach have also been highlighted, such as data availability and sharing protocols (Gupta et al, 2014). Comparative studies may be most effective where they can be used to test specific hypotheses.…”
Section: Sociohydrologic Datamentioning
confidence: 99%
“…The significant modification of the water cycle by human activity has primarily been treated as an external perturbation to such natural systems. However, externalizing the dependencies between human action and the availability, quality and dynamics of water clearly poses limitations to making predictions about water within the Anthropocene (Thompson et al, 2013). To address these limitations, a new generation of studies now focus on sociohydrology, which aims to understand the dynamics and co-evolution of coupled human-water systems (Sivapalan et al, 2012).…”
Section: Introductionmentioning
confidence: 99%